A new Malthopsis batfish from Taiwan, with comments on Malthopsis tiarella Jordan, 1902 (Lophiiformes: Ogcocephalidae) - Ho, Hsuan-Ching; Koeda, Keita (Zootaxa, 2019)
A new species of the triangular batfish genus Malthopsis Alcock, 1891 is described on the basis of 9 specimens collected from off Taiwan. The new species belongs to a species group with ventral surface covered by numerous small prickle-like bucklers. It differs from the members in this species group in having ventral surface entirely covered with tiny bucklers; principal bucklers on dorsal surface relatively tall, few in number and loose in arrangement; subopercle dull without enlarged forward-directed spine; rostral spine directed forward horizontally; 5 dorsal-fin rays and 12 pectoral-fin rays; and posterior tip of appressed anal fin not reaching caudal-fin base. Two specimens of Malthopsis tiarella Jordan, 1902 collected from Taiwan are recognized and its diagnosis is discussed.